Proceso de atención de enfermería en paciente femenino de 26 años con cálculo de conducto biliar más colangitis. - Iza Morejón, Luis Fernando (2024)
A clinical case is presented of an adult patient who was admitted to the emergency area of the Alfredo Noboa Montenegro Hospital for a clinical picture of abdominal pain located in the epigastrium and right hypochondrium for 3 days with a VAS of 6/10, accompanied by chills, headache, unquantified thermal rise and diarrheal stools. The objective of this case study is to establish a care plan applying the Nursing Care Process (NCP) in the patient through the description of the clinical history, health status, applied tests and identification of altered functional patterns. Cholangitis is an infection of the bile ducts, the tubes that carry bile from the liver to the gallbladder and intestines. Bile is a fluid produced by the liver that helps digest food. Its causes are usually caused by a bacterial infection. This can occur when the duct is blocked by something such as a gallstone or tumor. The infection causing this condition can also spread to the liver. Its most effective treatment endoscopic retrograde cholangiopancreatography is the gold standard and the treatment of choice for biliary decompression, as it is effective in 94 to 98% of cases.